Assessment of endometrial carcinoma on biopsy as a predictor of final surgical pathology: Are we doing it right? A completed audit cycle and recommendations - Aneeta Jassar; Nour Hemali; Anjali Bhatnagar (Indian Journal of Pathology and Microbiology)
Background: Typing and grading of endometrial carcinomas (ECs) on small biopsy specimens is crucial to determine the need for full surgical staging. Histological subtype and grade are key factors available for risk stratification before surgery. However, this can be diagnostically challenging on small biopsy specimens, especially when morphologic features are subtle or overlapping. Aims: The aims of this audit were to assess concordance of endometrial carcinomas on biopsy specimens with hysterectomy specimens and to determine if the immunohistochemistry (IHC) panel being used in our practice was adequately subtyping ECs. Settings and Design: The audit was approved by the Clinical Effectiveness Team of the Royal College of Pathologists (UK) as meeting all the criteria and standards set out by the College. Materials and Methods: Biopsies from 67 cases of EC were compared for histological subtype and grade of endometrioid carcinoma with resection specimens. A re-audit was carried out on 59 cases after implementation of changes recommended by the initial audit. Results: Two of 35 (6%) tumours defined as G1 on biopsy were upgraded (to G2) on final pathology, as was one of 7 (14%) G2 tumours (to G3). One of these cases had solid areas just amounting to more than 6% on resection. In the second case, a comment was made that assessment had been difficult as the specimen was suboptimally fixed, but nuclei appeared atypical. Of seven G2 biopsies, one case was upgraded to grade 3 on final pathology based on proportion of solid areas. Our data show lower rates of discordance as compared to previous studies and on re-audit, the concordance between endometrioid and nonendometrioid serous carcinoma improved with the addition of immunohistochemistry (IHC) for Phosphatase and tensin homolog (PTEN) to biopsies. Conclusions: PTEN IHC can complement other stains and aid in the distinction of grade 3 endometrioid carcinoma from serous carcinoma on endometrial biopsies.